The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.15448/1980-6108.2015.2.20351
|View full text |Cite
|
Sign up to set email alerts
|

Atividade angiogênica do óleo de sucupira (Pterodon emarginatus)

Abstract: Aims: To assess the angiogenic activity of sucupira (Pterodon emarginatus) oil, popularly used as an antirheumatic, analgesic, antimicrobial, and anti-inflammatory agent. Methods: The chick (Gallus domesticus) embryo chorioallantoic membrane (CAM) assay was used as an experimental model, incubated in a temperature-and humidity-controlled automatic incubator during the first five days. A circular hole was made at the wider base of the eggshell on the fifth day. After 13 days of incubation, filter paper discs co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
2
0
2
Order By: Relevance
“…Dutra et al (16) Juiz de Fora, Minas Gerais. Brasil De Araujo et al (18) Brasil, Goiânia/Goiás Denny (28) Avaliar a atividade antiinflamatória, antinociceptiva e A 500 mg/kg reduziu o edema induzido por bradicinina em 46% (após 15 minutos) (p<0,01). Apresentou atividade anti-inflamatória e antinociceptiva (terpenos).…”
Section: Resultados Principaisunclassified
“…Dutra et al (16) Juiz de Fora, Minas Gerais. Brasil De Araujo et al (18) Brasil, Goiânia/Goiás Denny (28) Avaliar a atividade antiinflamatória, antinociceptiva e A 500 mg/kg reduziu o edema induzido por bradicinina em 46% (após 15 minutos) (p<0,01). Apresentou atividade anti-inflamatória e antinociceptiva (terpenos).…”
Section: Resultados Principaisunclassified
“…cercárias de Schistosoma mansoni e também ações contra o Trypanosoma cruzi 3 . Além disso, são relatadas atividades antimicrobiana nas sementes, frutos e casca 11 , antiplaquetária 12 e angiogênica 13 .…”
Section: Introductionunclassified
“…Both species are economically important due to their medicinal use. They have pharmacological properties such as anti-inflammatory, analgesic, anti-tumor, and antimicrobial (Araújo et al 2015;Santos et al 2018). Herbal medicine laboratories growing interest in P. pubescens and P. emarginatus contributes to increased extractivism, predisposing these species to genetic diversity loss.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic diversity can be assessed by different genetic approaches, such as single nucleotide polymorphism (SNPs) and simple sequence repeats (SSR), also known as microsatellite markers. Few genetic studies involving species of Pterodon can be found in the literature, as the transferability of a few microsatellite markers from Phaseolus vulgaris L. and Dipteryx alata Vogel to Pterodon (Soares et al 2012;Santana 2014;Araújo et al 2015). Furthermore, there are no specifically developed microsatellite markers for Pterodon.…”
Section: Introductionmentioning
confidence: 99%